Environmentally driven sexual segregation in a marine top predator - Paiva, Vitor H. (Sci Rep, 2017)
Sexual segregation in foraging occurs in many animal species, resulting in the partitioning of resources and reduction of competition between males and females, yet the patterns and drivers of such segregation are still poorly understood. We studied the foraging movements (GPS-tracking), habitat use (habitat modelling) and trophic ecology (stable isotope analysis) of female and male Cory’s shearwaters Calonectris borealis during the mid chick-rearing period of six consecutive breeding seasons (2010–2015). We found a clear sexual segregation in foraging in years of greater environmental stochasticity, likely years of lower food availability. When food became scarce, females undertook much longer foraging trips, exploited more homogeneous water masses, had a larger isotopic niche, fed on lower trophic level prey and exhibited a lower body condition, when compared to males. Sexual competition for trophic resources may be stronger when environmental conditions are poor. A greater foraging success of one sex may result in differential body condition of pair mates when enduring parental effort, and ultimately, in an increased probability of breeding failure.